Natural environment effects on health and psychological well-being of people in Damansara City, Malaysia - Raman, Thivya Laxshmy (2021)
Malaysia is also on the verge of a mental deterioration wave. A large part of the day is spent in the workplace. Due to this, Malaysians are more vulnerable to mental illness. Malaysia's psychological well-being concerns have grown in the last two decades due to a lack of mindfulness of emotional well-being and cultural shame surrounding mental diseases. As a result, there is a real need for a technique for self-care that will promote psychological well-being during this period. Hence, the purposes of the study were to analyze the short-term effects of walking on diverse environmental conditions among working adults and give psychological information on the health outcomes of different urban green environments. The participants of this study where 80 working adults include males and females. The study area chosen for this study was Kota Damansara Community Forest Reserve, Mutiara Damansara Recreational Park, and Urban Green Corridor along Jalan PJU 7/2 was used as a control study site. All three study sites were visited in random order and on random weekends. Participants were asked to walk along a given route in three areas in which the time was set similarly three areas (30 minutes). Restorative effects that are measured: Depression, Anxiety and Stress Scale (DASS-21), Profile of Mood States (POMS) and Positive and Negative Affect Schedule (PANAS), and Restoration Outcome Scale (ROS) were used to identify psychological effects of different natural environments. The results indicated Kota Damansara Community Forest Reserve as an urban forested area and Mutiara Damansara Recreational Park as an urban park more effective in reducing stress. The restorative effects increased in all three green environments. The Kota Damansara Community Forest Reserve was chosen as most restorative than the other two. The recreational park was less restorative than urban forest but more restorative than the urban green corridor, which was at least restorative. The POMS test indicated a clear distinction of restorative effects in urban forested area and recreation park as the Total Mood Disturbance (TMD) of participants are negative, whereas in urban green corridor showed no changes. According to the PANAS test, participants showed an increase in positive attitude after took their walk at Kota Damansara Community Forest Reserve and Mutiara Damansara Recreational Park compare to the urban green corridor.